2016
DOI: 10.1002/ejlt.201600134
|View full text |Cite
|
Sign up to set email alerts
|

Pilot‐scale supercritical CO2 extraction of edible insect oil from Tenebrio molitor L. larvae – Influence of extraction conditions on kinetics, defatting performance and compositional properties

Abstract: In view of industrial fractionation processes for edible insects, supercritical CO2 extraction of Tenebrio molitor larval oil was studied. The influence of extraction parameters on defatting of larvae was investigated using a full factorial design. Furthermore, the effect of operating conditions on extraction kinetics, fatty acid composition, and acidity of mealworm oil was evaluated. Pressure, time, and their interaction showed the most significant effects on defatting. Maximal defatting (95%) was achieved at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 51 publications
(96 reference statements)
4
40
0
Order By: Relevance
“…Chemical composition of larvae [6,12,13,35,41]. The large heterogeneity of nutrient composition-even in the same species and metamorphic stage-can be ascribed to different diet, instar, origin, season, and gut content [7].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical composition of larvae [6,12,13,35,41]. The large heterogeneity of nutrient composition-even in the same species and metamorphic stage-can be ascribed to different diet, instar, origin, season, and gut content [7].…”
Section: Resultsmentioning
confidence: 99%
“…Extraction parameters were chosen according to the study of Purschke et al [35] and set to 400 bar, 45 °C, and 20 kg of CO 2 /h. The extractor was charged with 250 g of dried larvae.…”
Section: Partial Defatting By Supercritical Carbon Dioxide Extractionmentioning
confidence: 99%
“…Purschke et al. () studied supercritical CO 2 extraction of edible insect oil from T. molitor L. larvae. The authors found that T. molitor oil composition and acidity was influenced by the extraction parameters.…”
Section: Processing Technologiesmentioning
confidence: 99%
“…Some changes in protein composition were also found as a decrease in low-molecular fractions (15 to 20 kDa) and an increase in high-molecular fractions (>60 kDa; Bußler et al, 2016). Purschke et al (2017) studied supercritical CO 2 extraction of edible insect oil from T. molitor L. larvae. The authors found that T. molitor oil composition and acidity was influenced by the extraction parameters.…”
Section: Processing Technologies For Extractionmentioning
confidence: 99%
See 1 more Smart Citation